Emailing impact on e-learning engagement in a German start-up example - Tegmen, Devin (2021)
E-Learning engagement has gained importance within the past decade, not only due to the digitalization of learning through COVID-19 but socio-economic trends themselves. Therefore, this study is dedicated towards the usage of emailing as a tool to increase engagement analysing the applicability as well as the best possible strategies, in terms of email content and design. The underlying experiment involved 240 users of a digital learning platform which received emails over a time span of four weeks. The study reveals that providing users feedback on their learning path with a positive wording and design as the most beneficial possibility.